V-ATPase controls tumor growth and autophagy in a Drosophila model of gliomagenesis. Issue 12 (2nd December 2021) - Formica, Miriam; Storaci, Alessandra Maria; Bertolini, Irene; Carminati, Francesca; Knævelsrud, Helene; Vaira, Valentina; Vaccari, Thomas
ABSTRACT: Glioblastoma (GBM), a very aggressive and incurable tumor, often results from constitutive activation of EGFR (epidermal growth factor receptor) and of phosphoinositide 3-kinase (PI3K). To understand the role of autophagy in the pathogenesis of glial tumors in vivo, we used an established Drosophila melanogaster model of glioma based on overexpression in larval glial cells of an active human EGFR and of the PI3K homolog Pi3K92E/Dp110 . Interestingly, the resulting hyperplastic glia express high levels of key components of the lysosomal-autophagic compartment, including vacuolar-type H + -ATPase (V-ATPase) subunits and ref(2)P (refractory to Sigma P), the Drosophila homolog of SQSTM1/p62. However, cellular clearance of autophagic cargoes appears inhibited upstream of autophagosome formation. Remarkably, downregulation of subunits of V-ATPase, of Pdk1, or of the Tor (Target of rapamycin) complex 1 (TORC1) component raptor prevents overgrowth and normalize ref(2)P levels. In addition, downregulation of the V-ATPase subunit VhaPPA1-1 reduces Akt and Tor-dependent signaling and restores clearance. Consistent with evidence in flies, neurospheres from patients with high V-ATPase subunit expression show inhibition of autophagy. Altogether, our data suggest that autophagy is repressed during glial tumorigenesis and that V-ATPase and MTORC1 components acting at lysosomes could represent therapeutic targets against GBM.